ADVANCE Study: in patients with Type 2 diabetes mellitus, antihypertensive therapy decreases cardiovascular risk inde pendently of baseline blood pressure - I. E. Chazova (Кардиоваскулярная терапия и профилактика, 2008)
Blood pressure (BP) level is an important determinant of micro- and macrovascular complication risk in patients with Type 2 diabetes mellitus (DM-2). One of the aims of ADVANCE Study was, therefore, to assess the effects of Fixed-dose perindopril and indapamide (Noliprel®) combination, added to standard therapy, on cardiovascular, renal and other complication risk in DM-2 individuals. The four-year study included 11140 DM-2 patients taking Noliprel ®/Noliprel® forte or placebo, together with previously administered standard treatment. Additional therapy with Noliprel® was associated with the reduction in systolic and diastolic BP levels – by 5,6 and 2,2 mm Hg, respectively. Relative risk of main micro - and macrovascular complications decreased by 9%, and the risks of cardiovascular death, all-cause death and renal complications – by 18%, 14%, and 21%, respectively.